Association of Treatment Delays with Survival for Patients with Head and Neck Cancer Undergoing Surgery and Radiotherapy at the Philippine General Hospital - Nicole Sacayan-Quitay; Sean Patrick De Guzman; Johanna Patricia Cañal; Cesar Vincent Villafuerte (Philippine Journal of Otolaryngology Head and Neck Surgery)
Objective: To identify in what phases in the treatment of head and neck cancer do delays happen at a tertiary hospital and to determine the association between the length of treatment delays and the oncologic outcomes (disease-free survival and overall survival) for patients with head and neck cancer.